Severe heart failure and the need for mechanical circulatory support and heart transplantation in pediatric patients with myocarditis: Results from the prospective multicenter registry "MYKKE". (11th July 2019) - Schubert, Stephan; Opgen‐Rhein, Bernd; Boehne, Martin; Weigelt, Annika; Wagner, Robert; Müller, Götz; Rentzsch, Axel; zu Knyphausen, Edzard; Fischer, Marcus; Papakostas, Konstantin; Wiegand, Gesa; Ruf, Bettina; et al.
Abstract: Myocarditis represents an important cause for acute heart failure. MYKKE, a prospective multicenter registry of pediatric patients with myocarditis, aims to gain knowledge on courses, diagnostics, and therapy of pediatric myocarditis. The role of mechanical circulatory support (MCS) in children with severe heart failure and myocarditis is unclear. The aim of this study was to determine characteristics and outcome of patients with severe heart failure requiring MCS and/or heart transplantation. The MYKKE cohort between September 2013 and 2016 was analyzed. A total of 195 patients were prospectively enrolled by 17 German hospitals. Twenty‐eight patients (14%) received MCS (median 1.5 years), more frequently in the youngest age group (0‐2 years) than in the older groups ( P  < 0.001; 2‐12 and 13‐18 years). In the MCS group, 50% received a VAD, 36% ECMO, and 14% both, with a survival rate of 79%. The weaning rate was 43% (12/28). Nine (32%) patients were transplanted, one had ongoing support, and six (21%) died. Histology was positive for myocarditis in 63% of the MCS group. Patients within the whole cohort with age <2 years and/or ejection fraction <30% had a significantly worse survival with high risk for MCS, transplantation, and death ( P  < 0.001). Myocarditis represents a life‐threatening disease with an overall mortality of 4.6% in this cohort. The fulminant form more often affected the youngest, leading to significantly higher rate of MCS, transplantation, and mortality. MCS represents an important and life‐saving therapeutic option in children with myocarditis with a weaning rate of 43%.